RESPON SISWA TERHADAP MAJALAH BIOLOGI INVERTEBRATA SEBAGAI MEDIA PEMBELAJARAN DI KELAS X MIPA 2 - Rusnah Rusnah (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2022)
This study aims to determine the feasibility and response of students to invertebrate biology magazines as a learning media in class X MIPA 2 SMA Muhammadiyah 1 Pontianak. The research method applied in this research is descriptive. The form of descriptive research used in this research is a survey. The sample in this study were 16 students of class X MIPA 2 SMA Muhammadiyah 1 Pontianak. The instruments used were media validation sheets and student response questionnaires. Sources of data in this study were the results of the validation of the feasibility of the magazine media and the responses of class X MIPA 2 students to the media of invertebrate biology magazines. The results of the eligibility by the validator show that the magazine media is valid or suitable for use as a learning medium in class X MIPA SMA Muhammadiyah 1 Pontianak with an average CVR value of 0.99 with a very high validity level of 3.6. The results of student responses to the media of invertebrate biology magazines were 83.75% with a very strong category on the response criteria, and 82.64% on the reaction criteria with a very strong category, it can be concluded that the magazine learning media was declared valid with a student response of 82.92% and categorized as very strong